Economical Used-Oil Stove for Post-Harvest Energy in Agriculture - Mamangkai, Muhamad Khuldi; Sumual, Hendro Maxwell; Manongko, Jenly Dyliep Isria (Program Studi Teknik Pertanian Universitas Hasanuddin, 2025)
This study aims to develop and test the performance of energy-efficient stoves fueled by used oil as a renewable alternative energy solution for small-scale farmers. The stoves are designed to reduce dependence on subsidized Liquefied Petroleum Gas (LPG) while utilizing the increasing amount of oil waste in rural areas. The method used is Research and Development (R&D) with performance testing through the Water Boiling Test (WBT) and Fuel Consumption Rate (FCR) calculations. The main findings show that used oil stoves have an average thermal efficiency of 32.28%, meeting the SNI 7926:2013 standard (>30%), although slightly below the efficiency of LPG stoves (37.45%). These stoves are able to boil water 3-5 minutes faster than LPG stoves after reaching stable combustion conditions. From an economic perspective, the daily operating cost of used oil stoves is only Rp1,986, or 69.45% cheaper than LPG, and only consumes 4.9% of farmers' monthly income—far lower than LPG, which reaches 16%. With a production cost of IDR 363,000 per unit, this stove is not only affordable but also has the potential to reduce environmental impact through the utilization of waste oil. The research results indicate that used oil stoves are suitable for implementation as appropriate technology that supports energy security and the household economy of farmers.